The Mediating Role of Extrinsic Work Motivation on the Influence of Transformational Leadership and Organizational Climate on Employee Engagement Teachers - Ayep, Ayep; Nurhayati, Mafizatun; Utomo, Kabul Wahyu (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2024)
This study aims to analyze the mediating role of Extrinsic Work Motivation (EWM) in the influence of Transformational Leadership (TL) and Organizational Climate (OC) on Employee Engagement (EE). The population and sample in this study were all permanent teachers of Yayasan Bina Insan Mulia Batam Riau Islands, totaling 84 respondents. Sampling uses a non-probability sampling method, especially a saturated sampling method. This study used a survey method with a research instrument in the form of a questionnaire. The data analysis method was carried out with the Partial Least Square-Structural Equation Model (SEM PLS) 4.0.9.6. The results showed that TL had no direct and insignificant effect on EE, OC had a significant positive effect on EE, EWM had a significant positive effect on EE, TL had a significant positive effect on EWM, and OC had a significant effect on EE. EWM fully mediates the influence of TL on EE, and EWM partially mediates the influence of OC on EE. Transformational Leadership and Organizational Climate each contribute positively to teachers' Extrinsic Work Motivation. Furthermore, Extrinsic Work Motivation becomes a full mediator between Transformational Leadership and Employee Engagement, also partially mediating the relationship between Organizational Climate and teacher-employee engagement.